Implementasi Artificial Intelligence pada Sistem Pengawasan Pasien Rumah Sakit - Ondra Eka Putra (Jurnal Teknologi, 2020)
This study was conducted to create a system that can megawasi and detect temperature,noise, patients down from the bed in the patient's room in the hospital. This system is done by designing to create and implement system components including Arduino Mega as process controller, switch as emergency calling, LED and LCD to notify detected information, DHT11 sensor as temperature sensor, Sound sensor micropone as noise sensor, sensor loadcell as sensor weight and MP3 module as a sound notification, location detected in patient room in hospital. The results showed that the tool is made to function properly and can be used directly in place that requires.